2012
DOI: 10.1371/journal.pone.0031501
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Alzheimer's Disease Cerebrospinal Fluid

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive loss of cognitive functions. Today the diagnosis of AD relies on clinical evaluations and is only late in the disease. Biomarkers for early detection of the underlying neuropathological changes are still lacking and the biochemical pathways leading to the disease are still not completely understood. The aim of this study was to identify the metabolic changes resulting from the disease phenotype by a thorough and systematic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 35 publications
8
131
0
Order By: Relevance
“…One study has showed the increase of the concentrations of eight amino acids in AD versus MCI [111]. Another larger examination, after measuring 343 analytes has also led to detect eight molecules with statistical significance; interestingly, one of these markers, cortisol, correlated with the advancement of the disease [112]. A disadvantage with metabolomics as compared with proteomics and peptidomics may be that, in contrast to several proteins, there is no data showing an established role for small (non-protein) molecules in AD pathogenesis.…”
Section: Upcoming Candidate Biomarkersmentioning
confidence: 99%
“…One study has showed the increase of the concentrations of eight amino acids in AD versus MCI [111]. Another larger examination, after measuring 343 analytes has also led to detect eight molecules with statistical significance; interestingly, one of these markers, cortisol, correlated with the advancement of the disease [112]. A disadvantage with metabolomics as compared with proteomics and peptidomics may be that, in contrast to several proteins, there is no data showing an established role for small (non-protein) molecules in AD pathogenesis.…”
Section: Upcoming Candidate Biomarkersmentioning
confidence: 99%
“…The metabolic profile in human CSF samples of AD patients and agematched healthy controls unveils the presence of a significant presence of deregulated metabolites in AD cases [190]. Among them, higher corticols levels are found in AD cases, which correlate with AD progression and severity.…”
Section: Metabolic Profilementioning
confidence: 88%
“…3) indicates convergent variations in these pathways (Czech et al 2012). Importantly, the severity of the disease was correlated with decreased noradrenaline (Kaddurah-Daouk et al 2011b) and increased levels of vanillylmandelic acid, a degradation product of xanthine and dopamine (Kaddurah-Daouk et al 2013b).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Also, MSEA (Tab. 3) highlighted that two independent studies indicated alterations in methionine metabolism (Czech et al 2012;Ibanez et al 2012).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%